2013
DOI: 10.1136/medethics-2012-100975
|View full text |Cite
|
Sign up to set email alerts
|

The fox and the grapes: an Anglo-Irish perspective on conscientious objection to the supply of emergency hormonal contraception without prescription

Abstract: Emergency hormonal contraception (EHC) has been available from pharmacies in the UK without prescription for 11 years. In the Republic of Ireland this service was made available in 2011. In both jurisdictions the respective regulators have included 'conscience clauses', which allow pharmacists to opt out of providing EHC on religious or moral grounds providing certain criteria are met. In effect, conscientious objectors must refer patients to other providers who are willing to supply these medicines. Inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Despite the ful llment of the above-mentioned indications, one should not forget to present the patient with alternative options of obtaining a given drug from another pharmacist or in another pharmacy. This information is consistent both with the judgment of the European Court of Human Rights, which concerned the case of Pichon and Sajous v. France [6,7], and with the provisions of medical law in Great Britain, where the General Pharmaceutical Council (GPhC) veri es the circumstances of pharmacists invoking the clause conscience based on the review of fertility, conception and termination drugs [8,9].…”
Section: Discussionsupporting
confidence: 75%
“…Despite the ful llment of the above-mentioned indications, one should not forget to present the patient with alternative options of obtaining a given drug from another pharmacist or in another pharmacy. This information is consistent both with the judgment of the European Court of Human Rights, which concerned the case of Pichon and Sajous v. France [6,7], and with the provisions of medical law in Great Britain, where the General Pharmaceutical Council (GPhC) veri es the circumstances of pharmacists invoking the clause conscience based on the review of fertility, conception and termination drugs [8,9].…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, most pharmacists may not refuse (for whatever reason, e.g. no need to use, ethical aspects [25], etc.) to dispense EMCs if requested without prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kavanaugh et al 20 found that women who were not affiliated with a religion were more likely to be LARC users than those who were affiliated with a religion. These results may reflect the teaching of some religions that artificial means of contraception are unacceptable, including the possibility that health care providers may not comply with a patient's request for certain methods of contraception because of their own religious beliefs 32,33 . Health care providers need not only to be sensitive to a patient's religious beliefs when discussing contraceptive options but also to declare whether their own beliefs limit what they can recommend or prescribe.…”
mentioning
confidence: 84%